If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -1)(x + -2)(x + -2) + -1(x + -1) = 0 Reorder the terms: (-1 + x)(x + -2)(x + -2) + -1(x + -1) = 0 Reorder the terms: (-1 + x)(-2 + x)(x + -2) + -1(x + -1) = 0 Reorder the terms: (-1 + x)(-2 + x)(-2 + x) + -1(x + -1) = 0 Multiply (-1 + x) * (-2 + x) (-1(-2 + x) + x(-2 + x))(-2 + x) + -1(x + -1) = 0 ((-2 * -1 + x * -1) + x(-2 + x))(-2 + x) + -1(x + -1) = 0 ((2 + -1x) + x(-2 + x))(-2 + x) + -1(x + -1) = 0 (2 + -1x + (-2 * x + x * x))(-2 + x) + -1(x + -1) = 0 (2 + -1x + (-2x + x2))(-2 + x) + -1(x + -1) = 0 Combine like terms: -1x + -2x = -3x (2 + -3x + x2)(-2 + x) + -1(x + -1) = 0 Multiply (2 + -3x + x2) * (-2 + x) (2(-2 + x) + -3x * (-2 + x) + x2(-2 + x)) + -1(x + -1) = 0 ((-2 * 2 + x * 2) + -3x * (-2 + x) + x2(-2 + x)) + -1(x + -1) = 0 ((-4 + 2x) + -3x * (-2 + x) + x2(-2 + x)) + -1(x + -1) = 0 (-4 + 2x + (-2 * -3x + x * -3x) + x2(-2 + x)) + -1(x + -1) = 0 (-4 + 2x + (6x + -3x2) + x2(-2 + x)) + -1(x + -1) = 0 (-4 + 2x + 6x + -3x2 + (-2 * x2 + x * x2)) + -1(x + -1) = 0 (-4 + 2x + 6x + -3x2 + (-2x2 + x3)) + -1(x + -1) = 0 Combine like terms: 2x + 6x = 8x (-4 + 8x + -3x2 + -2x2 + x3) + -1(x + -1) = 0 Combine like terms: -3x2 + -2x2 = -5x2 (-4 + 8x + -5x2 + x3) + -1(x + -1) = 0 Reorder the terms: -4 + 8x + -5x2 + x3 + -1(-1 + x) = 0 -4 + 8x + -5x2 + x3 + (-1 * -1 + x * -1) = 0 -4 + 8x + -5x2 + x3 + (1 + -1x) = 0 Reorder the terms: -4 + 1 + 8x + -1x + -5x2 + x3 = 0 Combine like terms: -4 + 1 = -3 -3 + 8x + -1x + -5x2 + x3 = 0 Combine like terms: 8x + -1x = 7x -3 + 7x + -5x2 + x3 = 0 Solving -3 + 7x + -5x2 + x3 = 0 Solving for variable 'x'. The solution to this equation could not be determined.
| ln*24= | | Y=xy+2x-4 | | (5x+15)(x-8)=46 | | (5x+15)x(x-8)=46 | | (6xy^2/y)^-3 | | (6xy^2/y)^/3 | | -2(3x-1)=3(1-2x)+5 | | e^4x=23 | | 14=y/-7=19 | | 12=6(u+4)-8u | | 5x^2+43=(X+1)(5X-7) | | Y-3.29=.11(x-14) | | 12.8/6.25= | | 90x+-20=260 | | -6u+39=3(u-5) | | Y^2-8y-13=9y+28 | | -8x+5(x-8)=-16 | | y=x(660/3x) | | x(660/3x) | | 14=30+9v | | Y-26.5=2.45(x-8) | | 2(x-10)=14 | | -5(u+2)=6u-21 | | x^2-10ix+9i^2=0 | | 36=8u+6(u+8) | | 8K-1=63 | | 90x+-10=160 | | Y=2.45(x-8) | | 2+-14x=4 | | 3x+4y-8x-8y= | | 17=-4k-3 | | 9x+2a= |